Analisis Perbandingan Pendanaan Leasing dan Pembiayaan Bank Pada Pembelian Mobil Merek Toyota Avanza 1,3 E Std A/T (Studi Kasus Harga Mobil Toyota Avanza Terdaftar Bulan Mei 2018) - Rina Masithoh, Anang Setawan Titin Ruliana 2 (EKONOMIA, 2020)
ANANG SETIAWAN: Comparative Analysis of Leasing and Financing Bank for The Purchase of Toyota Avanza 1.3 E Std A / T , (Case study on Car Prices of Toyota Avanza Registered in May 2018. The purpose of this study is to find out which financing is the most profitable if it is compared with Present Value analysis tools for three years. The study was conducted at a leasing company PT Astra Credit companies (ACC) and a subsidiary of Mandiri Bank namely PT Mandiri Utama Finance (MUF) for three years from May 2018 to April 2021. The type of data used for this study was the installment data of motor vehicles obtained from each of these companies in early May 2018 using the comparison method. The data analysis tool used in conducting this research was present value. The results showed that within a period of 3 years with a Present Value analysis tool at PT Astra Credit Companies (ACC) of Rp.124,874,147, and the present value of financing of PT Mandiri Utama Finance Bank (MUF) of Rp.113,582,204, - .The conclusion of this study was financing through PT Mandiri Utama Finance (MUF) had a smaller Present Value (PV) value when compared to funding on leasing. Thus the Hypothesis was accepted.